Potencial de aproveitamento de microalgas Chlorella vulgaris e Scenedesmus subspicatus como matéria-prima para obtenção de biodiesel - Novaes Junior, Sidney de Oliveira (2013)
This study aimed to assess the potential growth of two species of microalgae ( Chlorella vulgaris and Scenedesmus subspicatus ) in two types of effluents ( humans and pigs ) in order to obtain lipids that could be converted into biodiesel . Such compounds must meet the specifications contained in Resolution No. 07 / 2008 of ANP . The effluents were collected in human Station Wastewater Treatment III , located in the city of Foz do Iguaçu / PR and swine effluent in Granja São Jorge ( Colombari ) , located in the municipality of São Miguel do Iguaçu / PR . Both were sent to laboratories for analysis IAP and NUCLEOTEC constatassem that the presence of nitrogenous and phosphatic and oils and greases total , respectively. The effluents were diluted to previously autoclaved and which can serve as culture media for microorganisms . They were then inoculated samples of each type of microalgae in an effluent and evaluated their growth. In four vials was added the compound mineral Agrostemin ® to assess their influence on the results . Prepared growth curves after 60 days of cultivation samples were filtered under vacuum for further extraction of oils using ultrasound. The samples were sent for analysis of lipid content and composition in terms of fatty acids by gas chromatography , which demonstrated the presence of fatty acids that make up biodiesel . The physico-chemical characterization of the effluent showed the presence of small amounts of fats and greases in both the total effluent . The quantitative analysis of lipids showed the highest concentration in the cultivation of C. vulgaris in human effluent , with 50.12 % . With the addition of Agrostemin ®, the yield was better in the cultivation of S. subspicatus in swine wastewater , with 80% increase in the production of lipids , followed by the growth of C. vulgaris in human effluent , with 41 % . The acids were higher concentrations linoleic (C18 : 2) , the cultivation of C. vulgaris in human effluent with 35.17 % , followed by the arachidic ( 20:0 ) with the same microalgae , now in swine wastewater , with 37.29 % , the palmitoleic ( C16 : 1 ) arising from the cultivation of S. subspicatus in human effluent , with 28.85% and pentadecanoic ( C15 : 1 ), the culture of the same organism in swine wastewater , with 55.22 % . It was found that the latter is what gives the best results, but the viability of the remainder is also promising.